PENGARUH PENGAWASAN MELEKAT, PENGAWASAN FUNGSIONAL, PENGAWASAN PREVENTIF, PENGAWASAN DETEKTIF DAN PENGANGGARAN BERBASIS KINERJA TERHADAP EFEKTIVITAS PENGENDALIAN ANGGARAN (Studi Empiris Pada SKPD Provinsi Riau) - Voadhe Dendi; Kamaliah '; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted on employees SKPD Riau Province. This research was included in the quantitative research. The type of data used in this research is the primary data by source. And then, in data collections sampling was conducted with a purposive sampling method (Sugiyono,2012: 392) with respondents as many as 81 employees who working in SKPD Riau Province. Data were analyzed using multiple regression with SPSS version 20.This research aimed to know the influence of the Attached Supervision, Functional Supervision, Preventive Supervision, Detective Supervision and Performance-baced Budgeting to the Effectiveness of budget control. The main problem that researcher descriptions are as follows: to see how many significant relationship between the dependent variable to the independent variable.The results of this research showed that Attached Supervision influence to the Effectiveness of budget control, Functional Supervision does not affect to the Effectiveness of budget control, Preventive Supervision does not affect to the Effectiveness of budget control, Detective Supervision does not affect to the Effectiveness of budget control and Performance-baced Budgeting does not affect to the Effectiveness of budget control.Keywords: Effectiveness of budget control, Attached Supervision, Functional Supervision, Preventive Supervision, Detective Supervision.